Group learning : the impact of group personality and psychological safety on group performance. - Chiang, Jing Ying. (2013)
The formation of permanent and temporary work groups in the employment landscape has resulted in higher education institutions incorporating intensive group learning in their curriculum. However, the limited empirical research performed on temporary groups to understand group processes on group performance have intrigued the studying of temporary groups in academic setting.